Cigarette consumption among university students in Montenegro: the prevalence and smoking habits: Cigarette consumption among university students - Boskovic, Vasilije; Vlaovic Boskovic, Jelena; Ljaljevic, Agima; Babovic, Batric; Slovic, Zivana; Corovic, Snezana; Nenadovic, Aleksandar; Mihaljevic, Olgica B (Medicinski časopis, 2022)
Objective. The aim of this study was to determine the prevalence of cigarette consumption and the differences in smoking habits among university students aged 18–26 years from different faculties in Montenegro. Method. This cross-sectional study was conducted in University of Montenegro in Podgorica and the data were collected using a structured questionnaire. Results. The study enrolled 146 students of both gender (63 males and 83 females) with an average age of 21.63 ± 2.16 years. It was shown that overall prevalence of cigarete consumption was 52.05% among all participants i.e. 21.62% among the students of Faculty of Medicine (p < 0.001). Among the students who experienced smoking, 46.57% of them stated that it was in the period of high school. We did not estimate a significant difference in the daily smoking frequency (number of cigarettes per day) (p = 0.443). Also, study participants did not have a specific time during the day for cigarette consumption (67.20%). The largest number of students (40.70%) light the first cigarette after more than half an hour of waking up. University students believed that cigarette smoking could overcome stressful situations, and improved concentration and memory. Smoking status was found to be higher among the students of older age (p < 0.001) and advancing year of faculty (p = 0.002). The analysis showed no significantly gender difference in smoking habits. Conclusion. Our investigation confirmed a high prevalence of cigarette consumption among university students in Montenegro, and therefore we recommend the developing of appropriate programs for smoking prevention and cessation.